A reflex electron beam discharge as a plasma source for electron beam generation - Rocca, Jorge J., author; Murray, Chris S., author; Szapiro, B., author; IEEE, publisher (Colorado State University. Libraries, 1988)
A reflex electron beam glow discharge has been used as a plasma source for the generation of broad-area electron beams. An electron current of 120 A (12 A/cm2) was extracted from the plasma in 10 μs pulses and accelerated to energies greater than 1 keV in the gap between two grids. The scaling of the scheme for the generation of multikiloamp high-energy electron beams is discussed.